2010
DOI: 10.1590/s0104-56872010000400031
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da aclimatização no reconhecimento de fala: avaliação sem as próteses auditivas

Abstract: There was a progressive reduction of sentences recognition thresholds and signal/noise ratios indicating an improvement in performance even when assessing the individuals without the hearing aids. This improvement can be related to the effect of acclimatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Another study also it evaluated the communicative performance by means of the determination of IPRSS 23 e, in the same way, observed improvement of this in the presence of the amplification, as the observed one in the present work.…”
Section: Discussionsupporting
confidence: 84%
“…Another study also it evaluated the communicative performance by means of the determination of IPRSS 23 e, in the same way, observed improvement of this in the presence of the amplification, as the observed one in the present work.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study conducted tests of Sentences Recognition Thresholds in Noise and in Silence, before the hearing aid fitting, after two weeks of use and after three months of use. 80% of the participants presented improvement between the first and the second evaluation, and 82.5%, between the first and the third, indicating the influence of acclimatization on the improvement in auditory processing tests 31 . Another study, already mentioned, has brought the same findings: the SSW test was performed by individuals with sensorineural hearing loss, some without hearing aid fitting and some already wearing HA for from 4 months to 6 years.…”
Section: Resultsmentioning
confidence: 93%
“…Another study with 31 elders found significant relation between daily use of hearing devices and enhancement in the social interaction, evidencing that the more a patient wears his/her hearing aid, the better his/her communicative performance (27) . This improvement can be related to the acclimatization effects, when progressive improvement in hearing skills occur, according to a study with 40 participants, between 28 and 78 years of age, with mild to moderately severe sensorineural hearing loss, which evidenced progressive improvement in speech understanding in quiet and noisy settings, after 14 days and three months of use (28) .…”
Section: Discussionmentioning
confidence: 99%